Molecular characterization of a Minus-C odorant-binding protein from Cyrtotrachelus buqueti (Coleoptera: Curculionidae) - Liu, Long; Li, Yangdi; Yang, Hua; Wang, Fan; Huang, Qiong (Frontiers in Physiology, 2025)
Odorant-binding proteins (OBPs) are important for insects to discriminate, bind and transport odorants, such as pheromones and host plant volatiles. Herein, the Minus-C OBP (CbuqOBP1) was characterized from Cyrtotrachelus buqueti, one of the most important pests in bamboo plantations. CbuqOBP1 showed significantly higher transcription levels in the adult stage and was most highly expressed in the head of both sexes, the thorax and antenna of the male, indicating that it plays important roles in chemosensory behavior of adults and may also function in other biological processes. Fluorescence competitive binding assays showed that CbuqOBP1 displayed broad binding capabilities and strong affinities to phenol (Ki = 10.49 μM) and benzothiazole (Ki = 11.11 μM) among 8 C. buqueti volatiles. CbuqOBP1 also showed high binding affinity to the main volatile of the host plant Neosinocalamus affinis (linalool, Ki = 13.41 μM). The docking results indicated that hydrophobic interactions were the prevailing forces between CbuqOBP1 with these three ligands. Additionally, several amino acid residues were significantly overlapped and contributed to the interactions with the ligands. The combined results suggest that CbuqOBP1 may play dual roles in binding volatile compounds from the host plant and the same species and will be helpful to developing new pest-control strategies.